TEACHING READING BY USING ANNOTATING TEXT STRATEGY TO IMPROVING STUDENTS’ READING COMPREHENSION OF ELEVENTH GRADERS AT SMA NEGERI 3 PAGARALAM - M Bambang Purwanto (Journal of English Education, Literature and Linguistics, 2022)
The title of this thesis is Teaching Reading by Using Annotating Text Strategy to Improving Students’ Reading Comprehension of Eleventh Graders at SMA Negeri 3 Pagar Alam. The problem of this study was there any significant improvment of the student’s reading comprehension who were taught by used Annotating Text Strategy and those who were not to the eleventh graders of SMA Negeri 3 Pagar Alam. The objective of this study was to identify whether or not the used of Annotating Text Strategy was effective to improved the students' reading comprehension. The test was used in this study with 10 meetings of treatment including pre-test and post-tests. The population was 188 taken from all of eleventh grade students of SMA Negeri 3 Pagaralam in academic years 2017/2018. The sample was 66 students were taken by purposive sampling technique. The writer took the sample from 2 classes; they were XI IPA 1 as an experimental group and XI IPA 2 as control group. Quasi experimental method was applied. The data was selected by using multiple choice and consist 30 (thirty) of quesions . The data were analyzed by using paired Sample t test and independent t test. The result of paired sample t-test found t-obtained 3.763 with significant 0.000 it was higher than t-table was 2.654. It means that the alternative hypothesis (Ha) was accepted and the null hypothesis (Ho) was rejected. It can be concluded there was Annotating Text Strategy improved students’ in teaching reading comprehension on Narrative text.